Monovision slows juvenile myopia progression unilaterally - Phillips, J R (Copyright 2005 British Journal of Ophthalmology, 2005)
Aim: To evaluate the acceptability, effectivity, and side effects of a monovision spectacle correction designed to reduce accommodation and myopia progression in schoolchildren. Methods: Dominant eyes of 11 year old children with myopia (−1.00 to −3.00 D mean spherical equivalent) were corrected for distance; fellow eyes were uncorrected or corrected to keep the refractive imbalance ⩽2.00 D. Myopia progression was followed with cycloplegic autorefraction and A-scan ultrasonography measures of vitreous chamber depth (VCD) for up to 30 months. Dynamic retinoscopy was used to assess accommodation while reading. Results: All children accommodated to read with the distance corrected (dominant) eye. Thus, the near corrected eye experienced myopic defocus at all levels of accommodation. Myopia progression in the near corrected eyes was significantly slower than in the distance corrected eyes (inter-eye difference = 0.36 D/year (95% CI: 0.54 to 0.19, p = 0.0015, n = 13); difference in VCD elongation = 0.13 mm/year (95% CI: 0.18 to 0.08, p = 0.0003, n = 13)). After refitting with conventional spectacles, the resultant anisometropia returned to baseline levels after 9–18 months. Conclusions: Monovision is not effective in reducing accommodation in juvenile myopia. However, myopia progression was significantly reduced in the near corrected eye, suggesting that sustained myopic defocus slows axial elongation of the human eye.